Groundwater governance: The illegality of exploitation and ways to minimize the problem - CONICELLI,BRUNO (2021)
Abstract In Brazil, there are about 2.5 million tubular wells in which 88% of them are illegal, extracting more than 17,580 Mm3/yr. This irregular use may cause sustainability issues that may be economic, social, or environmental (overexploitation, well losses and associated increases of water conflicts; aquifer contamination; and land subsidence). This paper aims to address the illegal wells in Brazil and discuss measures to minimize it. Conclusions indicate that users do not understand the aquifer dynamic and, therefore, do not have a proper understanding of problems such as loss of water quality and quantity caused by the excess of groundwater exploitation. This creates a false idea that there are no water conflicts among users, which causes a lack of engagement by society. Without groundwater users and stakeholder pressure, the government does not aim to control or close illegal wells, and the “vicious cycle” persists. The one way to break this “vicious cycle” would be programs of social communication and users’ participation, coupled with improvements to the control apparatus and inspection from State institutions, making sure that there is correct management and not only legislations that are not applied.